Pengaruh Fraud Diamond dan Religiusitas terhadap Kecurangan Akademik Mahasiswa Akuntansi - Lulu Amalia Nusron; Risa Tika Sari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Higher education is expected to be able to produce professionals who are able to compete in the era of globalization both in science and in morals, however fraudulent practices are often found in the world of education which is often referred to as academic fraud. This study aims to determine the factors that influence student academic fraud by using the fraud diamond concept and religiosity. Collecting data in this study using online questionnaires and purposive sampling techniques with the criteria of active students who have taken auditing courses 2. The sample of this study was 80 active students of the Accounting Study Program at Universitas PGRI Yogyakarta, Universitas Negeri Yogyakarta, Universitas Muhammadiyah Yogyakarta, Universitas Teknologi Yogyakarta, and Universitas Sanata Dharma Yogyakarta. Data analysis techniques using multiple linear regression models and data testing using SPSS. The results of this study indicate that opportunity and rationalization have a significant positive effect on academic cheating while pressure, capability, and religiosity have no effect on academic cheating.